The Effectiveness of Using the Google Form Application on Completing Student Assignments with Project-Based Learning - A. Nongko, Pahenra; La Ndibo, Yaman; Said, Hasmira; Rohmiati, Rohmiati; Saranani, Muhammad Saifuddin (Sinergi International Journal of Education, 2024)
This study focuses on the needs of holistic and integrated 21st century learning to develop thinking skills in stages. The low achievement of Indonesian education, as shown by the results of the Program for International Student Assessment (PISA), confirms that only a few students have high-level thinking skills. This study aims to describe the effectiveness of using Google Forms based on Project-Based Learning (PjBL) in increasing student activity in making course assignments. The method used is a quasi-experimental design with a single group pre-test and post-test design. The results of the study indicate that the use of Google Forms based on PjBL is effective in increasing student activity and creativity in completing assignments. The implication of this study is that the use of digital media such as Google Forms can be a useful tool in supporting the learning process, especially in increasing activity and creativity in various courses.